FUNGSI, KEDUDUKANDAN PERBANDINGAN HADITS DENGAN AL- QUR’AN - Abdul Wahab Syakhrani; Ahmad Fahri (CV. Adiba Aisha Amira, 2024)
The science of hadith is the science that discusses the rules to determine the position of sanad and matan, whether accepted or rejected. According to Tengku Muhammad Hasbi AshShiddieqy: